Advances in long-acting slow effective release antiretroviral therapies for treatment and prevention of HIV infection - Soriano, Vicente; Ullah Nayan, Mohammad; Sillman, Brady; Hasan, Mahmudul; Deodhar, Suyash; Das, Srijanee; Sultana, Ashrafi; Thai Hoang Le, Nam; Edagwa, Benson; Gendelman, Howard E. (Advanced Drug Delivery Reviews, 2024)
Adherence to daily oral antiretroviral therapy (ART) is a barrier to both treatment and prevention of human immunodeficiency virus (HIV) infection. To overcome limitations of life-long daily regimen adherence, longacting (LA) injectable antiretroviral (ARV) drugs, nanoformulations, implants, vaginal rings, microarray patches, and ultra-long-acting (ULA) prodrugs are now available or in development. These medicines enable persons who are or at risk for HIV infection to be treated with simplified ART regimens. First-generation LA cabotegravir, rilpivirine, and lenacapavir injectables and a dapivirine vaginal ring are now in use. However, each remains limited by existing dosing intervals, ease of administration, or difficulties in finding drug partners. ULA ART regimens provide an answer, but to date, such next-generation formulations remain in development. Establishing the niche will require affirmation of extended dosing, improved access, reduced injection volumes, improved pharmacokinetic profiles, selections of combination treatments, and synchronization of healthcare support. Based on such needs, this review highlights recent pharmacological advances and a future treatment perspective. While first-generation LA ARTs are available for HIV care, they remain far from ideal in meeting patient needs. ULA medicines, now in advanced preclinical development, may close gaps toward broader usage and treatment options.
Keywords: long-acting slow effective release antiretroviral therapy; pre-exposure prophylaxis; human immunodeficiency virus; antiretroviral prodrugs; pharmacokinetic testing; adverse reactions; medicinal and polymer chemistry; pharmacodynamics; nucleoside reverse transcriptase inhibitors; Nonnucleoside reverse transcriptase inhibitors; Integrase strand transfer inhibitors; JCR